Study of a wide-aperture combined deformable mirror for high-power pulsed phosphate glass lasers. (28th December 2015) - Samarkin, V V; Aleksandrov, A G; Jitsuno, T; Romanov, P N; Rukosuev, A L; Kudryashov, A V
Abstract: A deformable mirror with the size of 410 × 468 mm controlled by bimorph piezoceramic plates and multilayer piezo stacks is developed. The response functions of individual actuators and the measurements of the flatness of the deformable mirror surface are presented. The study of mirrors with an interferometer and a wavefront sensor has shown that it is possible to improve the surface flatness down to a residual roughness of 0.033 μm (RMS). The possibility of correction of beam aberrations in an ultra-high-power laser using the created bimorph mirror is demonstrated.